ELECTROCOAGULATION CONTROL SYSTEM DESIGN IN TEXTILE WASTEWATER TREATMENT PLANT - Nazuwatussya'Diyah
The development of textile industry is also followed by increasing amount of textile wastewater produced. It will potentially harm the environment. Possible solution for this problem is wastewater treatment. Electrocoagulation is used for the treatment, in this research. Electrocoagulation is one of coagulation method using direct current for electrolysis. In this research, two kinds of PI controller to maintain turbidity with setpoint of 100 NTU. One of them is designed with modified electric current and the another one is designed with modified flowrate. In the end of this research, both of the controller will be campared to determine which one is more suitable to the system. Energy consumption and settling time will be assigned as the parameters for the comparison. First order equation with time delay will be used to interpret and identify the system. The controller’s tuning will be done by the method of Ziegler Nichols with the electric current input between 1,8-5,2 Ampere and flow input of 10,37-14,67 ml/s. This research shows controlled system with modified electric current variable needed approximately 28 minutes to reach its stability with energy consumption of 42,175 kJ. On the other hand, controlled system with modified fluid’s flow variable just needed 26 minutes to reach its stability by consuming 61,229 kJ.